Dufour and Soret Effects on Mixed Convection Flow Past a Vertical Porous Flat Plate with Variable Suction - Alam, M. S.; Rahman, M. M. (Nonlinear Analysis: Modelling and Control, 2006)
In this paper the Dufour and Soret effects on mixed convection flow past a vertical porous flat plate embedded in a porous medium have been studied numerically. The governing non-linear partial differential equations have been transformed by a similarity transformation into a system of ordinary differential equations, which are solved numerically by applying NachtsheimSwigert shooting iteration technique together with sixth order Runge-Kutta integration scheme. For fluids of medium molecular weight (H2, air), profiles of the dimensionless velocity, temperature and concentration distributions are shown graphically for various values of suction parameter fw, Dufour number Du and Soret number Sr. Finally, numerical values of physical quantities, such as the local skin-friction coefficient, the local Nusselt number and the local Sherwood number are presented in tabular form.